Basic Theories, Methods of Formation and Determination of Potential in the Education System - Murodova, Zarina Rashidovna; Boltayev, Sherzod Jamolovich (International Journal of Human Computing Studies, 2022)
Information Technology to adequately study and formulate their thinking skills in this field. Because, as the day goes by, Information Systems, which are fundamental for information technology, are constantly developing and being enriched with various modes, technologies. This requires repeated study and a certain amount of time, if the potential for knowledge and skills learned in the school is not formed.